The future of endovascular treatment: Insights from the ESCAPE investigators. Issue 2 (February 2016) - Klourfeld, Evgenia; Zerna, Charlotte; Al-Ajlan, Fahad S; Kamal, Noreen; Randhawa, Privia; Yu, Amy Y; Dowlatshahi, Dar; Thornton, John; Williams, David; Holmstedt, Christine; Kelly, Michael; Frei, Donald; et al.
The ESCAPE trial demonstrated strong morbidity benefit and mortality reduction for endovascular stroke treatment. Following the release of the main results, the ESCAPE trial investigators convened at a 2-day close-out meeting in March 2015 in Banff, Alberta, Canada. Meeting discussions focused on system implications, procedural characteristics, and future directions. We report the proceedings of the meeting, which provide insights from the trialists into the issues of generalizability, treatment limitations, as well as future directions and opportunities in stroke care optimization.